Carbon-based catalyst, PTFE (Polytetrafluoroethylene) catalytic filter material as well as preparation method and application of PTFE catalytic filter material
The preparation of catalytic filter material by using the carbon-based catalyst CQDs-MnCe/C and PTFE blending method is solved, and the low temperature activity and easy loss of catalysts are achieved, and the low temperature synergistic removal of multiple pollutants in the flue gas and the reduction of equipment costs are achieved.
Patent Information
- Application Number
- CN202411250073.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-09-06
AI Technical Summary
In the existing flue gas treatment technology, the catalyst has low low temperature activity and is prone to loss, resulting in low temperature synergistic removal efficiency of particulate matter, volatile organic matter and nitrogen oxide in the incinerated flue gas is not high.
The carbon-based catalyst CQDs-MnCe/C and polytetrafluoroethylene resin (PTFE) blending method was used to prepare catalytic filter materials. The acidic and active sites of the catalyst were strengthened by carbon quantum dots (CQDs), which improved the low-temperature catalytic activity, and enhanced the binding strength of the catalyst and the filter cloth through a binder.
The low temperature synergistic removal of particulate matter, VOCs and NOx in the incinerated flue gas is achieved, which improves the bonding strength of the catalyst, reduces the loss rate of the catalyst, and reduces the investment cost of the flue gas treatment equipment.
Smart Images

Figure CN119500107A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flue gas pollution control, and in particular to a carbon-based catalyst, a PTFE catalytic filter material, and a preparation method and application thereof. Background Art
[0002] The existing waste incineration flue gas treatment process steps are as follows: semi-dry reaction tower, bag dust removal, selective catalytic reduction reactor and spray tower, etc. If the dust removal bag can be upgraded to have catalytic function, the subsequent flue gas control equipment can be reduced.
[0003] Patent CN114225936B "Denitration catalyst for waste incineration flue gas and its preparation method" provides a reaction temperature window of 200-300℃ for the denitration catalyst, but it is still higher than the incineration flue gas (<200℃), and additional equipment is required to perform secondary heating of the flue gas, which increases the cost of flue gas treatment. Patent CN113304550B "A method for preparing a multifunctional composite filter material for dust removal and denitration" provides a method for preparing a multifunctional composite filter material for dust removal and denitration. After preparing a catalytic filter membrane by loading a composite transition metal oxide catalyst onto the surface of a breathable base membrane using molecular self-assembly, it is hot-pressed and composited with a filter material base cloth. However, polytetrafluoroethylene resin has strong chemical stability, and the combination of the catalyst and the filter material is still mainly physical adsorption, with weak bonding strength, and the catalyst is easy to peel off. Therefore, it is necessary to develop a catalyst and catalytic filter material preparation technology for the coordinated control of multiple pollutants to overcome the problems of low catalyst activity at low temperatures (<200℃) and easy loss of the catalyst during use. Summary of the invention
[0004] In order to solve at least one of the above problems, the present invention provides a carbon-based catalyst, a PTFE catalytic filter material, and a preparation method and application thereof. The catalytic filter material prepared by the method of the present invention has a tighter combination of the catalyst and the filter cloth, which can ensure that particulate matter, volatile organic compounds (VOCs), nitrogen oxides (NO x )'s low-temperature synergistic removal efficiency.
[0005] In order to achieve the above object, the present invention adopts the following technical means:
[0006] A first aspect of the present invention provides a method for preparing a carbon-based catalyst, comprising the following steps:
[0007] (1) Preparation of carbon-based carriers
[0008] The biomass, the nitrogen-containing activator and the foaming activator are uniformly mixed in a mass ratio of (0.5-1.5):(1-5):(1-5), placed in a muffle furnace, and calcined at a temperature of 700-1000° C. for 1-3 hours to obtain a carbon-based carrier;
[0009] (2) Active component loading
[0010] A manganese metal precursor, a cerium metal precursor and a carbon-based carrier are added to an aqueous solution in a mass ratio of (0.5-1.5): (0.5-1.5): (5-12), stirred at room temperature for 1-5 hours, then dried at 90-110° C., and calcined at 250-350° C. for 2-6 hours under a calcination atmosphere to obtain a MnCe / C catalyst;
[0011] (3) Carbon quantum dots (CQDs) optimization
[0012] Dissolve glucose in aqueous solution, add sodium hydroxide solution, perform ultrasonic treatment for 1-6 hours, adjust the pH to neutral with acid solution, add an equal volume of ethanol solution, and obtain a mixed solution A;
[0013] The MnCe / C catalyst and the mixed solution A were added to the aqueous solution at a mass volume ratio of 1 g: (0.3-1) ml, stirred at room temperature for 25-35 min, and then dried at 90-110° C. to obtain a carbon-based catalyst: CQDs-MnCe / C catalyst.
[0014] In some embodiments of the present invention, the biomass in step (1) is one of wheat straw, corn straw, yellow bamboo, pine wood, corn cob, and α-cellulose; the nitrogen-containing activator can be one or more of ammonium oxalate, urea, and ammonium nitrate; the foaming activator can be one or more of sodium bicarbonate or potassium bicarbonate. Preferably, the biomass is α-cellulose, the nitrogen-containing activator is ammonium oxalate, and the foaming activator is sodium bicarbonate.
[0015] In some embodiments of the present invention, the calcination atmosphere in step (1) is one of nitrogen, air and vacuum.
[0016] In some embodiments of the present invention, the manganese metal precursor in step (2) is one or more of manganese sulfate, manganese nitrate, manganese carbonate, and manganese acetate; the cerium metal precursor is one or more of cerium nitrate, cerium sulfate, and cerium carbonate. Preferably, the manganese metal precursor is manganese nitrate, and the cerium metal precursor is cerium nitrate.
[0017] In some embodiments of the present invention, the concentration of the sodium hydroxide solution in step (3) is 1 to 3 mol / L, preferably, the concentration of the sodium hydroxide solution is 1 mol / L.
[0018] In some embodiments of the present invention, the acid solution in step (3) is one of nitric acid, hydrochloric acid and sulfuric acid. Preferably, the acid solution is hydrochloric acid, and the concentration of the acid solution is 2 mol / L.
[0019] The second aspect of the present invention provides a method for preparing a PTFE catalytic filter cloth, wherein the catalytic filter cloth is prepared by combining a CQDs-MnCe / C catalyst prepared by the method described in the first aspect with a PTFE filter cloth by a blending and drawing method, and the steps are as follows: an auxiliary agent and a polytetrafluoroethylene resin are uniformly mixed in a mass ratio of (0.1-2): (0.5-2), and the mixture is allowed to stand at 70°C for 24-48 hours, and then the mixture is taken out and extruded into a cylindrical shape at a pressure of 3Mpa, and a PTFE calendered film is obtained by a calendering step at 40-80°C, and then a thin layer of adhesive is applied on the surface of the calendered film and 25wt%-35wt% of the CQDs-MnCe / C catalyst is sprayed on it, and finally the PTFE catalytic filter cloth is obtained by longitudinal drawing, slitting, curling and needle punching steps.
[0020] In some embodiments of the present invention, the auxiliary agent is one of white oil, aviation kerosene, liquid paraffin or petroleum ether; the binder is one of coal tar, organic titanium coupling agent or epoxy resin adhesive. Preferably, the auxiliary agent is white oil and the binder is epoxy resin adhesive.
[0021] The third aspect of the present invention provides a PTFE catalytic filter cloth prepared according to the method described in the second aspect.
[0022] The CQDs-MnCe / C catalyst prepared by the method described in the first aspect and the PTFE catalytic filter cloth described in the third aspect are used in the preparation of a catalyst for synergistically controlling particulate matter, VOCs and NO in incineration flue gas. x Application in products.
[0023] Beneficial effects of the present invention
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention provides a carbon-based catalyst, CQDs-MnCe / C catalyst, which is used as the catalytic active component of the catalytic filter material, and the metal-metal interaction between Mn and Ce is used to achieve the regulation of surface acid sites and active sites, and the large specific surface area and multi-level pore structure of biochar are used to promote the degradation of VOCs and NO x The adsorption and transformation of pollutants such as VOCs and NOx can be effectively improved by strengthening the regeneration of acidic sites and active sites through CQDs, where CQDs act as ultrafast electron transmission channels to promote the low-temperature transformation of pollutants.
[0026] (2) The catalytic filter material of the present invention combines the catalyst with the filter cloth by a binder, so that the catalyst is present on the fiber surface, the bonding strength between the catalyst and the filter cloth is enhanced, and the loss rate of the catalyst during use is reduced. At the same time, the problem of the catalyst being wrapped in the conventional blending and drawing method, which affects the physical properties of the filter cloth and the weak catalytic performance, is avoided.
[0027] (3) When the catalytic filter cloth of the present invention is used, there is no need to add or modify equipment. It only needs to replace the filter material on the existing bag-type dust removal equipment to achieve coordinated control of multiple pollutants and effectively reduce the investment cost of flue gas pollution control equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Shown is a flow chart for preparing PTFE catalytic filter material;
[0029] Figure 2 A schematic diagram of a catalytic performance evaluation device is shown; wherein, 1. a nitrogen cylinder, 2. an oxygen cylinder, 3. a nitric oxide cylinder, 4. an ammonia cylinder, 5-9. a mass flow meter, 10. a bubbling tank, 11. a mixing tank, 12. a tubular furnace, 13. a gas chromatograph, 14. a flue gas analyzer, and 15. a PTFE catalytic filter material.
[0030] Figure 3 This is a diagram showing the catalytic performance of the catalytic filter material prepared in Examples 1-3 of the present invention for the synergistic removal of chlorobenzene and NO.
[0031] Figure 4 This is a diagram showing the catalytic performance of the catalytic filter material prepared in Examples 3-5 of the present invention for the synergistic removal of chlorobenzene and NO.
[0032] Figure 5 This is a diagram showing the catalytic performance of the catalytic filter materials prepared in Example 3 of the present invention and Comparative Example 1 for the synergistic removal of chlorobenzene and NO.
[0033] Figure 6 These are SEM images of Example 3 and Comparative Example 1 of the present invention; wherein a, Example 1, b, Comparative Example 1. DETAILED DESCRIPTION
[0034] The following examples are used to demonstrate preferred embodiments of the present invention. It will be appreciated by those skilled in the art that the techniques disclosed in the following examples represent techniques discovered by the inventors that can be used to implement the present invention and therefore can be considered as preferred embodiments of the present invention. However, it will be appreciated by those skilled in the art based on this specification that many modifications may be made to the specific embodiments disclosed herein and still achieve the same or similar results without departing from the spirit or scope of the present invention.
[0035] The present invention discloses a carbon-based catalyst, a PTFE catalytic filter material, and a preparation method and application thereof. The catalytic filter material can be used to synergistically control particulate matter, VOCs and NO in incineration flue gas. x The specific preparation steps of the catalytic filter material are as follows: Figure 1As shown below: the catalyst is prepared through the steps of carbon-based carrier preparation, active component loading, CQDs optimization, etc., and then the catalyst is sprayed on the PTFE calendering membrane with a binder as a connecting bridge, and a catalytic filter material with a strong bond between the catalyst and the filter cloth is formed through the steps of longitudinal drawing, slitting, curling, and needle punching.
[0036] A method for preparing a carbon-based catalyst comprises the following steps:
[0037] (1) Preparation of carbon-based carriers
[0038] The biomass, the nitrogen-containing activator and the foaming activator are uniformly mixed in a mass ratio of (0.5-1.5):(1-5):(1-5), and calcined at a temperature of 700-1000° C. for 1-3 hours to obtain a carbon-based carrier; wherein the biomass is one of wheat straw, corn straw, yellow bamboo, pine wood, corn cob, and α-cellulose; the nitrogen-containing activator is one or more of ammonium oxalate, urea, and ammonium nitrate; and the foaming activator is one or more of sodium bicarbonate or potassium bicarbonate;
[0039] (2) Active component loading
[0040] A manganese metal precursor, a cerium metal precursor and a carbon-based carrier are added to an aqueous solution in a mass ratio of (0.5-1.5): (0.5-1.5): (5-12), stirred at room temperature for 1-5 hours, and then dried at 90-110° C., and calcined at 250-350° C. for 2-6 hours under a calcination atmosphere to obtain a MnCe / C catalyst; wherein the manganese metal precursor is one or more of manganese sulfate, manganese nitrate, manganese carbonate, and manganese acetate; the cerium metal precursor is one or more of cerium nitrate, cerium sulfate, and cerium carbonate; and the calcination atmosphere is one of nitrogen, air, and vacuum;
[0041] (3) Carbon quantum dot optimization
[0042] Dissolve glucose in aqueous solution, add sodium hydroxide solution with a concentration of 1-3 mol / L, perform ultrasonic treatment for 1-6 hours, adjust the pH to neutral with an acid solution, add an equal volume of ethanol solution to obtain a mixed solution A; the acid solution is one of nitric acid, hydrochloric acid, and sulfuric acid, and the concentration of the acid solution is 2 mol / L;
[0043] The MnCe / C catalyst and the mixed solution A were added to the aqueous solution at a mass volume ratio of 1 g: (0.3-1) ml, stirred at room temperature for 25-35 min, and then dried at 90-110° C. to obtain a carbon-based catalyst: CQDs-MnCe / C catalyst.
[0044] (4) Catalyst and PTFE calendering film composite
[0045] The additive and polytetrafluoroethylene resin are mixed evenly in a mass ratio of (0.1-2): (0.5-2), and the mixture is allowed to stand at 70°C for 24-48 hours. Then, the mixture is taken out and extruded into a cylindrical shape under a pressure of 3Mpa. The PTFE calendered film is obtained through a calendering step at 40-80°C. Then, a thin layer of adhesive is coated on the surface of the calendered film and a certain mass of CQDs-MnCe / C catalyst is sprayed on it. Finally, the PTFE catalytic filter cloth is obtained through longitudinal drawing, slitting, curling and needle punching steps, wherein the additive is one of white oil, aviation kerosene, liquid paraffin or petroleum ether; and the adhesive is one of coal tar, organic titanium coupling agent or epoxy resin adhesive.
[0046] The catalytic performance evaluation device includes a nitrogen cylinder 1, an oxygen cylinder 2, a nitric oxide cylinder 1, an ammonia cylinder 4, mass flow meters 5-9, a bubbling tank 10, a mixing tank 11, a tubular furnace 12, a gas chromatograph 13, a flue gas analyzer 14, and a PTFE catalytic filter material 15. Figure 2 The connection structures shown are connected via pipelines, and the PTFE catalytic filter material 15 is located in the tubular furnace 12 .
[0047] The test process is as follows: install the catalytic filter material to be tested in the catalytic reactor, open all gas cylinders 1-4 and the tubular furnace 12, adjust the concentration of each pollutant in the reaction atmosphere, and pass it into the tubular furnace 12 after the concentration of each pollutant in the reaction atmosphere is stable, and use the gas chromatograph 13 and the flue gas analyzer 14 to detect the concentration of each pollutant in the tail pipe.
[0048] The catalyst content and loss of the catalytic filter material are calculated based on the weight of the filter cloth before and after use.
[0049] The technical solution of this patent is further described in detail below in conjunction with specific implementation methods, and the specific implementation methods are not intended to limit the scope of protection.
[0050] Example 1
[0051] The specific preparation steps of the catalytic filter material of this embodiment are as follows:
[0052] (1) Preparation of carbon-based carriers
[0053] Alpha-cellulose, ammonium oxalate and sodium bicarbonate were uniformly mixed in a mass ratio of 1:3:3 and placed in a muffle furnace and calcined at a calcination temperature of 900° C. for 1 h to obtain a carbon-based carrier.
[0054] (2) Active component loading
[0055] Manganese nitrate, cerium nitrate and carbon-based carrier were added to 50 ml of aqueous solution in a mass ratio of 1:1:10, stirred at room temperature for 1 hour, then dried at 105°C, and finally calcined at 300°C for 4 hours under a calcination atmosphere to obtain a MnCe / C catalyst.
[0056] (3) Carbon quantum dots (CQDs) optimization
[0057] 6 g of glucose was dissolved in 50 ml of aqueous solution, and then 50 ml of sodium hydroxide solution (1 mol / L) was added, and ultrasonic treatment was performed for 1 h. Then, the pH was adjusted to neutral with 2 mol / L hydrochloric acid solution, and finally an equal volume of ethanol solution was added to obtain a mixed solution A. 1 g of MnCe / C catalyst and 0.5 ml of mixed solution A were added to 30 ml of aqueous solution, stirred at room temperature for 30 min, and then dried at 105 ° C to obtain a CQDs-MnCe / C catalyst.
[0058] (4) Catalyst and PTFE calendering film composite
[0059] White oil and PTFE resin were mixed evenly in a weight ratio of 0.5:4, allowed to stand at 70°C for 24 hours, and then the mixture was taken out and extruded into a cylindrical shape under a pressure of 3 MPa. The PTFE calendered membrane was obtained through a calendering step at 40°C. A thin layer of epoxy resin adhesive was then applied on the surface of the calendered membrane and 10 wt% of the CQDs-MnCe / C catalyst was sprayed on the PTFE calendered membrane. Finally, the PTFE catalytic filter cloth was obtained through longitudinal drawing, slitting, curling and needle punching steps.
[0060] The catalyst content of the PTFE catalytic filter material prepared by the above method is 65.2 g / m 2 .
[0061] Example 2
[0062] The steps for preparing the catalytic filter material in this embodiment are similar to those in embodiment 1, except that the catalyst spraying amount in step (5) is increased to 20 wt %. The catalyst content of the PTFE catalytic filter material prepared by the above method is 121.9 g / m 2 .
[0063] Example 3
[0064] The steps for preparing the catalytic filter material in this embodiment are similar to those in Example 1, except that the catalyst spraying amount in step (5) is increased to 30 wt %. The catalyst content of the PTFE catalytic filter material prepared by the above method is 210.6 g / m 2 .
[0065] Example 4
[0066] The steps for preparing the catalytic filter material in this embodiment are similar to those in embodiment 3, except that the ratio of 1 g of MnCe / C catalyst to 0.5 ml of mixed solution A added to 30 ml of aqueous solution in step (4) is adjusted to 1 g of MnCe / C catalyst to 1 ml of mixed solution A added to 30 ml of aqueous solution. The catalyst content of the PTFE catalytic filter material prepared by the above method is 213.4 g / m 2.
[0067] Example 5
[0068] The steps for preparing the catalytic filter material in this embodiment are similar to those in Example 1, except that the ratio of 1 g of MnCe / C catalyst to 0.5 ml of mixed solution A added to 30 ml of aqueous solution in step (4) is adjusted to 1 g of MnCe / C catalyst to 0.3 ml of mixed solution A added to 30 ml of aqueous solution. The catalyst content of the PTFE catalytic filter material prepared by the above method is 209.1 g / m 2 .
[0069] Comparative Example 1
[0070] The difference from Example 3 is that this example adopts a blending and drawing method to prepare the catalytic filter material: the MnCe / C catalyst, white oil, and PTFE resin in step (4) are uniformly mixed in a weight ratio of 1.2:0.5:4, and then the catalytic filter material is prepared through extrusion, calendaring, stretching, acupuncture and other steps. The catalyst content of the PTFE catalytic filter material prepared by the above method is 181.2 g / m 2 .
[0071] Catalytic performance analysis
[0072] The catalytic filter materials prepared in Examples 1-5 and Comparative Example 1 were placed in a catalytic performance evaluation device, the equipment was turned on, and the performance of the catalytic filter materials was analyzed with a total flow rate of 100 ml / min, 100 ppm chlorobenzene, 500 ppm NO, 500 ppm NH3, 11 vol% oxygen, and the balance nitrogen in the reaction atmosphere.
[0073] (1) The catalytic performance of the catalytic filter materials prepared in Examples 1-5 for the synergistic removal of chlorobenzene and NO is as follows: Figure 3 and Figure 4 As shown, the results show that the catalytic filter material prepared in Example 3 has the highest synergistic removal ability for NO and chlorobenzene, and the lowest T90 temperature.
[0074] Depend on Figure 3 By comparing Examples 1-3, it can be seen that the amount of catalyst sprayed has a great influence on the synergistic removal ability of chlorobenzene and NO, which can be mainly attributed to the influence of the amount of catalyst sprayed on the catalyst loading in the catalytic filter material.
[0075] Depend on Figure 4By comparing Examples 3-5, it can be seen that an appropriate amount of CQDs can effectively increase the electron transfer speed of the filter material and enhance the low-temperature catalytic activity of the catalytic filter material, while excessive CQDs loading may cover the catalytic active sites, thereby inhibiting the low-temperature catalytic activity of the catalytic filter material. The chlorobenzene removal rates of the catalytic filter material at 180°C are: Example 3 (94.0%) > Example 5 (86.5%) > Example 4 (59.2%), and the NO conversion rates are: Example 3 (100%) > Example 5 (98.2%) > Example 4 (93.2%).
[0076] (2) The catalytic performance of the catalytic filter materials prepared in Example 3 and Comparative Example 1 in synergistically removing chlorobenzene and NO is as follows: Figure 5 The SEM images of the catalytic filter materials prepared in Example 3 and Comparative Example 1 are shown as follows: Figure 6 As shown,
[0077] The results show that the catalytic effect of the catalytic filter material prepared in Comparative Example 1 is much lower than that of the catalytic filter material prepared in Example 3, and the catalytic filter material of the present application has a better low-temperature synergistic catalytic effect of chlorobenzene and NO.
[0078] It can be seen from the SEM image that the catalyst of comparative example 1 is partially coated with PTFE, while the catalyst of example 3 mainly exists on the PTFE surface, so that the surface catalytic active sites of example 3 are significantly more than those of comparative example 1, and thus the low-temperature catalytic performance of comparative example 1 is relatively lower than that of example 3.
[0079] (3) The catalyst content and loss of the catalytic filter material are shown in Table 1 below.
[0080] Table 1 Changes in catalyst content of catalytic filter material
[0081] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 <![CDATA[Before performance analysis (g / m 2 )]]> 65.2 121.9 210.6 213.4 209.1 181.2 <![CDATA[After performance analysis (g / m 2 )]]> 60.6 115.7 204.9 205.5 205.2 164.6 <![CDATA[Catalyst loss (g / m 2 )]]> 4.6 6.2 5.7 7.9 3.9 16.6
[0082] By comparing Examples 1-3, it can be seen that the amount of catalyst sprayed has a greater impact on the catalyst content. The amount of catalyst sprayed in Example 3 has the highest catalyst loading. Compared with Example 2, Example 3 has a higher loading and a smaller catalyst loss. In Examples 3-5, the introduced CQDs content is different. Although the difference in loading and catalyst loss is not too large, there are differences in the low-temperature catalytic activity of the catalytic filter material for chlorobenzene and NO. Figure 4 It can be seen that Example 3 has a higher low-temperature catalytic activity.
[0083] By comparing Example 3 and Comparative Example 1, it is found that the binder can effectively improve the bonding strength between the catalyst and the filter material and reduce the catalyst loss of the catalytic filter material during use. Although part of the catalyst in Comparative Example 1 is coated with PTFE, the uncoated catalyst on the surface is easily lost.
[0084] However, when the catalyst spraying amount is higher, the initial catalyst COD removal rate will increase appropriately, the catalyst is easily lost during use, and the removal rate decreases rapidly.
[0085] (4) The particle removal performance of the catalytic filter material is shown in Table 2 below.
[0086] Table 2 Particle removal rates of Examples 1-5 and Comparative Example 1
[0087] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Particle removal rate (%) 99.9 99.9 99.9 99.9 99.9 99.9
[0088] By comparing Examples 1-5 with Comparative Example 1, it can be seen that the catalyst spraying amount and the CQDs loading amount have no significant effect on the particle removal performance of the filter material, and the removal rate of the catalytic filter material can reach 99.9%.
[0089] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field may make some substitutions and improvements to some technical features therein according to the disclosed technical content without departing from the principles of the present invention. These substitutions and improvements should also be regarded as within the protection scope of the present invention.
Claims
1. A method for preparing a carbon-based catalyst, characterized in that: The steps include: (1) Preparation of carbon-based carriers The biomass, the nitrogen-containing activator and the foaming activator are uniformly mixed in a mass ratio of (0.5-1.5):(1-5):(1-5), and calcined at a temperature of 700-1000° C. for 1-3 hours to obtain a carbon-based carrier; (2) Active component loading A manganese metal precursor, a cerium metal precursor and a carbon-based carrier are added to an aqueous solution in a mass ratio of (0.5-1.5):(0.5-1.5):(5-12), stirred at room temperature for 1-5 hours, then dried at 90-110° C., and calcined at 250-350° C. for 2-6 hours under a calcination atmosphere to obtain a MnCe / C catalyst; (3) Carbon quantum dot optimization Dissolve glucose in aqueous solution, add sodium hydroxide solution, perform ultrasonic treatment for 1-6 hours, adjust the pH to neutral with acid solution, add an equal volume of ethanol solution, and obtain a mixed solution A; The MnCe / C catalyst and the mixed solution A were added to the aqueous solution at a mass volume ratio of 1 g: (0.3-1) ml, stirred at room temperature for 25-35 min, and then dried at 90-110° C. to obtain a carbon-based catalyst: CQDs-MnCe / C catalyst.
2. The method for preparing a carbon-based catalyst according to claim 1, characterized in that: In step (1), the biomass is one of wheat straw, corn straw, yellow bamboo, pine wood, corn cob, and α-cellulose; the nitrogen-containing activator is one or more of ammonium oxalate, urea, and ammonium nitrate; and the foaming activator is one or more of sodium bicarbonate or potassium bicarbonate.
3. The method for preparing a carbon-based catalyst according to claim 1, characterized in that: In step (2), the manganese metal precursor is one or more of manganese sulfate, manganese nitrate, manganese carbonate, and manganese acetate; the cerium metal precursor is one or more of cerium nitrate, cerium sulfate, and cerium carbonate; and the calcination atmosphere in step (2) is one of nitrogen, air, and vacuum.
4. The method for preparing a carbon-based catalyst according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step (3) is 1-3 mol / L.
5. The method for preparing a carbon-based catalyst according to claim 1, characterized in that: The acid solution in step (3) is one of nitric acid, hydrochloric acid and sulfuric acid.
6. A method for preparing a catalytic filter cloth, characterized in that: The catalytic filter cloth is prepared by combining the CQDs-MnCe / C catalyst prepared by the method according to any one of claims 1 to 5 with a polytetrafluoroethylene filter material by a blending and drawing method, and the steps are as follows: the auxiliary agent and the polytetrafluoroethylene resin are mixed evenly in a mass ratio of (0.1-2): (0.5-2), and the mixture is allowed to stand at 70° C. for 24-48 hours, and then the mixture is taken out and extruded into a cylindrical shape under a pressure of 3Mpa, and a PTFE calendering film is obtained by a calendering step at 40-80° C., and then a thin layer of adhesive is applied on the surface of the calendering film and 25wt%-35wt% of the CQDs-MnCe / C catalyst is sprayed on it, and finally the PTFE catalytic filter cloth is obtained by longitudinal drawing, slitting, curling and needle punching.
7. The method for preparing a catalytic filter cloth according to claim 6, characterized in that: The auxiliary agent is one of white oil, aviation kerosene, liquid paraffin or petroleum ether.
8. The method for preparing a catalytic filter cloth according to claim 6, characterized in that: The binder is one of coal tar, organic titanium coupling agent or epoxy resin adhesive.
9. A catalytic filter cloth prepared according to the method according to any one of claims 7-8.
10. Use of the carbon-based catalyst prepared by the method according to any one of claims 1 to 5 and the catalytic filter cloth according to claim 9 in removing volatile organic compounds, nitrogen oxides and particulate matter products.
Citation Information
Patent Citations
A method for preparing a multifunctional composite filter material for dust removal and denitrification
CN113304550B
Low-temperature SCR (Selective Catalytic Reduction) catalyst based on active coke loaded manganese-cerium composite oxide and preparation method of low-temperature SCR catalyst
CN103433034A
Preparation method of carbon quantum dot modified denitration catalyst
CN111185178A
Smart bed with air improvement and multimedia features
KR1020200141827A
Novel methods for creation of sub-micron biocarbon materials from biomass and their fields of application
WO2018085918A1